A pilot study of disulfiram for individuals with persistent symptoms despite prior antibiotic treatment for Lyme disease - Kuvaldina, Mara; Preston, Jessica; McClellan, Denise; Pavlicova, Martina; Brannagan, Thomas H.; Fallon, Brian A. (Frontiers in Medicine, 2025)
IntroductionIn vitro studies report that disulfiram is effective in killing Borrelia burgdorferi. Case series suggest disulfiram may help to reduce the symptoms of patients with persistent symptoms despite prior antibiotic treatment for Lyme disease. This pilot study assessed safety, tolerability, and signs of clinical response.Materials and methodsParticipants with a history of previously treated Lyme disease and persistent fatigue were randomly assigned in a double-blinded fashion to either Group A (disulfiram for 4 weeks and placebo for 4 weeks) or Group B (disulfiram for 8 weeks). Primary outcome endpoint was at 10 weeks with a follow-up at 14 weeks. The primary aim was to assess safety and tolerability. A clinical aim assessed signs of clinical improvement using well-validated measures, focusing on improvement in fatigue and quality of life. Target enrollment was 24 participants.Results940 individuals were screened, 11 were enrolled and nine participated in the trial. Dosing started low and increased based on response and tolerance to a maximum of 500 mg daily. Safety. Two participants discontinued medication due to clinical worsening, one of whom was briefly hospitalized. Three additional participants were withdrawn from treatment due to lab test abnormalities. Tolerability. Only three of nine participants completed the full course of treatment (two in Group A and one in Group B). Lower doses were better tolerated than the highest dose. Clinical response. Of nine participants, clinically meaningful improvement was noted in fatigue for six and in quality of life for four. Among the six fatigue responders, improvement was also noted on a multiple domain symptom index (six of six), overall symptom burden (five of six), and functional impairment (four of six). The study was terminated early due to end of project funding, higher than expected adverse events, and recognition that sufficient information was gathered to inform future studies.Conclusions and relevanceThis study reveals the risks associated with disulfiram, especially at higher doses, while suggesting potential clinical benefits among some participants. Efficacy could not be assessed given the small sample size and the lack of a placebo-control group.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT03891667?cond=Lyme%20Disease&intr=disulfiram&rank=1, NCT03891667.